LANGUAGE TEACHING CHALLENGES THROUGH THE LENS OF CORPUS LINGUISTICS - Lőrincz, Marianna Levrints (TEFLIN Journal, 2024)
The present study explored the dominant discourses of language teaching challenges by utilizing methods associated with corpus linguistics and probed for the validity of the applied methodological design. The gleanings were obtained based on a specialized corpus (638,312 tokens) of journal articles pertinent to the designated topic sourced from leading journals in the field. By deploying keywords, collocation and n-grams analyses, substantiated by qualitative interpretation of quantitative data, the study evinced the prevalent themes related to language teaching challenges. The corpus foregrounded the challenges in the areas of teacher education and development, with a special emphasis on the professional initiation phase. Research domains addressing challenges of language learning and proficiency, language teaching methodology, professional and emotional aspects of language teaching were found to be lexically rich. Additionally, heightened research attention was documented for challenges associated with language learners, language policy and sociocultural factors, and the integration of technology in language education. In all, the applied research procedure has proven a sound methodology capable of signposting the salient themes and concepts tackled in academic publications, given the numerous parallels drawn between the results of the present and previous studies.